Immunogenicity and Antigenicity of Rabbit Hepatitis E Virus-Like Particles Produced by Recombinant Baculoviruses - Bai, Huimin; Kataoka, Michiyo; Ami, Yasushi; Suzaki, Yuriko; Takeda, Naokazu; Muramatsu, Masamichi; Li, Tian-Cheng (Viruses, 2021)
Rabbit hepatitis E virus (HEV) is a novel HEV belonging to genotype 3 (HEV-3) in the Orthohepevirus A species of the genus Hepevirus, family Hepeviridae. Rabbit HEV was originally isolated from rabbits and found to cause zoonotic infection. Although rabbit HEV can be successfully grown in culture with several cell lines, including the human carcinoma cell line PLC/PRF/5, it is difficult to obtain the large amounts of viral antigen required for diagnosis and vaccine development. In this study, we expressed N-terminal 13 and 111 aa-truncated rabbit HEV ORF2 proteins using recombinant baculoviruses and obtained two types of virus-like particles (VLPs), RnVLPs and RsVLPs with ~35 and 24 nm diameter, respectively. Anti-rabbit HEV IgG antibodies were induced in high titer by immunizing rabbits with RnVLPs or RsVLPs. The antibody secretion in the serum persisted more than three years. RsVLPs showed stronger antigenic cross-reactivity against HEV-1, HEV-3 and HEV-4 than rat HEV. Moreover, anti-RsVLPs antibodies neutralized not only the cognate virus but also HEV-1, HEV-3 and HEV-4 ex vivo, indicating that rabbit HEV had the same serotype as human HEVs. In contrast, the antibody did not block rat HEV infection, demonstrating that rat HEV belonged to a different serotype. Animal experiments indicated that immunization with either RnVLPs or RsVLPs completely protected the rabbits from challenge by rabbit HEV, suggesting that the VLPs are candidates for rabbit HEV vaccine development.